U–Th–Ra variations in Himalayan river sediments (Gandak river, India): Weathering fractionation and/or grain-size sorting?. (15th November 2016) - Bosia, Clio; Chabaux, François; Pelt, Eric; France-Lanord, Christian; Morin, Guillaume; Lavé, Jérôme; Stille, Peter
Abstract: Understanding the origin of U–Th–Ra variations in the Ganga river sediments is a prerequisite for correctly using U-series nuclides to constrain the sediment transport times in Himalayan rivers. For this purpose, U, Th, and Ra concentrations, along with 238 U– 234 U– 230 Th– 226 Ra radioactive disequilibria, were analyzed in bank, bedload and suspended sediments from the Gandak river, one of the main tributaries of the Ganga river. The data confirm that U and Th budgets of the Himalayan sediments are significantly influenced by minor resistant minerals, such as zircon, garnet and Ti-bearing minerals, the dissolution of which required the use of a high-pressure acid digestion process. Most importantly, the results indicate that the variations in ( 238 U/ 232 Th) and ( 230 Th/ 232 Th) activity ratios and 238 U– 234 U– 230 Th– 226 Ra disequilibria in sediments along the river alluvial plain mainly reflect modifications in the mineralogical and grain-size compositions rather than the degree of weathering during transport. The ( 238 U/ 232 Th) and ( 230 Th/ 232 Th) activity ratios in the bank and bed sediments are related to variations in the minor primary minerals strongly enriched in U and Th (i.e., zircon, REE-bearing minerals and Ti-bearing minerals), whereas the activity ratios in the suspended load are related to variations in the proportions of clay, Fe-oxyhydroxides and the silt-sand fraction, which contains U- and Th-bearing minor minerals. The data also indicate that 238 U– 234 U– 230 Th– 226 Ra disequilibria are strongly influenced by secondary mineral phases: the 230 Th budget is likely mainly controlled by Fe-oxyhydroxides, and the 226 Ra budget is likely mainly controlled by clay minerals. Therefore, the variations in the 238 U– 234 U– 230 Th– 232 Th system in the sediments of the Gandak river cannot simply be interpreted as the result of fractionation due to chemical transformation of the bulk sediment during its transport within the alluvial plain and/or the result of radioactive decay. Consequently, they cannot be used to infer long sediment transport times within the Gandak plain (10–100 ka), as previously proposed. Such analytical and interpretative artifacts are certainly not specific to the present study on the Gandak basin. These issues will certainly be encountered anytime this technique is applied to alluvial systems in which the U and Th budgets of the sediments are influenced by "heavy" minerals that can be sorted during the transport of sediments within the plain.